Fault Diagnosis for Current Sensors in Charging Modules Based on an Adaptive Sliding Mode Observer - Pengfei Huang; Jie Liu; Jiaxin Wang (Sensors, 2025)
This article proposes a fault diagnosis method based on an adaptive sliding mode observer (SMO) for current sensors (CSs) in the charging modules of DC charging piles. Firstly, we establish a model of the phase-shift full-bridge (PSFB) converter with CS faults. Secondly, the fault of the CS is reconstructed through system augmentation and non-singular coordinate transformation. Then, an adaptive SMO is designed to estimate the reconstructed state, and the residual between the actual value of the reconstructed state and the observed value is used as the fault detection variable. Finally, by using norms to design adaptive thresholds and comparing them with fault detection variables, the diagnosis of incipient faults, significant faults, and failure faults in CSs can be achieved. The experimental results verify the effectiveness of the proposed method in this paper; the robustness of the method has been verified under the conditions of DC voltage fluctuations and load fluctuations.